Formyl peptide receptor 2 regulates dendritic cell metabolism and Th17 cell differentiation during neuroinflammation - Lim, Jong-Hyung; Neuwirth, Ales; Chung, Kyoung-Jin; Grossklaus, Sylvia; Soehnlein, Oliver; Hajishengallis, George; Chavakis, Triantafyllos (Frontiers in Immunology, 2024)
Formyl peptide receptor 2 (FPR2) is a receptor for formylated peptides and specific pro-resolving mediators, and is involved in various inflammatory processes. Here, we aimed to elucidate the role of FPR2 in dendritic cell (DC) function and autoimmunity-related central nervous system (CNS) inflammation by using the experimental autoimmune encephalomyelitis (EAE) model. EAE induction was accompanied by increased Fpr2 mRNA expression in the spinal cord. FPR2-deficient (Fpr2KO) mice displayed delayed onset of EAE compared to wild-type (WT) mice, associated with reduced frequencies of Th17 cells in the inflamed spinal cord at the early stage of the disease. However, FPR2 deficiency did not affect EAE severity after the disease reached its peak. FPR2 deficiency in mature DCs resulted in decreased expression of Th17 polarizing cytokines IL6, IL23p19, IL1β, and thereby diminished the DC-mediated activation of Th17 cell differentiation. LPS-activated FPR2-deficient DCs showed upregulated Nos2 expression and nitric oxide (NO) production, as well as reduced oxygen consumption rate and impaired mitochondrial function, including decreased mitochondrial superoxide levels, lower mitochondrial membrane potential and diminished expression of genes related to the tricarboxylic acid cycle and genes related to the electron transport chain, as compared to WT DCs. Treatment with a NO inhibitor reversed the reduced Th17 cell differentiation in the presence of FPR2-deficient DCs. Together, by regulating DC metabolism, FPR2 enhances the production of DC-derived Th17-polarizing cytokines and hence Th17 cell differentiation in the context of neuroinflammation.